Financial Planning Strategy of "Container Villa Rental Company in the Mountains" in Indonesia - Edward Makaronna Sinulingga; Tanti Yanuar Rahmad; Rhian Indradewa; Muhammad Dhafi Iskandar (Jurnal Syntax Admiration, 2023)
The development of the tourism industry in Indonesia has presented new business opportunities, including in the field of container villa rental in mountainous areas. This business promises attractive potential, but is also faced with various challenges related to proper financial planning. This research aims to analyze and understand the financial planning strategies adopted by container villa rental companies in Indonesia's mountainous regions. This research uses a qualitative approach with a case study method. The data in this study was collected through in-depth interviews with relevant parties in the container villa rental company, including financial management and other decision makers. In addition, data is also collected through document studies, namely financial reports, budgets, and company business plans. The collected data will be analyzed with a qualitative approach. The results show that financial planning for container villa rental companies in the mountains in Indonesia needs to be done systematically and structured. Financial planning in villa container rental companies in the mountains includes financial goals and objectives, financial planning elements, financial projections, investment feasibility analysis, and financial performance analysis.